Improvement Voltage Profile of Kurdistan Power System By Using SVC/STATCOM - Suzan Fuad Wahhab; Aree Akram Muhammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The surge in demand for electricity has driven the power system to operate at a lower efficiency level. With the many actions taken to improve the electric grid, voltage unbalance and line overload have become challenging problems to address. Voltage control can be determined in generation, transfer, and electricity usage. When the power system is under stress, reactive current unbalance significantly contributes to voltage instability. To maximize the efficiency of a power system, flexible transmission systems system (FACTS) devices must be used most effectively and feasible. FACTS devices like Static VAR Compensators (SVCs) and Static Synchronous Compensators (STATCOMs) can reduce instability in heavily burdened lines, resulting in lower system losses and more excellent network reliability. In this paper, FACTS controllers such as SVC and STATCOM are incorporated in the Kurdistan power system simulated by using PSAT software based on MATLAB for the improvement of voltage profile, minimization of the system losses, and cost of the system. Also, the graphical comparisons of the results are presented to investigate the effectiveness of the proposed methods.